Genome‐wide off‐target analyses of CRISPR/Cas9‐mediated T‐cell receptor engineering in primary human T cells. Issue 1 (23rd January 2022) - Kaeuferle, Theresa; Stief, Tanja A; Canzar, Stefan; Kutlu, Nayad N; Willier, Semjon; Stenger, Dana; Ferrada‐Ernst, Paulina; Habjan, Nicola; Peters, Annika E; Busch, Dirk H; Feuchtinger, Tobias
Abstract: Objectives: Exploiting the forces of human T cells for treatment has led to the current paradigm of emerging immunotherapy strategies. Genetic engineering of the T‐cell receptor (TCR) redirects specificity, ablates alloreactivity and brings significant progress and off‐the‐shelf options to emerging adoptive T‐cell transfer (ACT) approaches. Targeted CRISPR/Cas9‐mediated double‐strand breaks in the DNA enable knockout or knock‐in engineering. Methods: Here, we perform CRISPR/Cas9‐mediated TCR knockout using a therapeutically relevant ribonucleoprotein (RNP) delivery method to assess the safety of genetically engineered T‐cell products. Whole‐genome sequencing was performed to analyse whether CRISPR/Cas9‐mediated DNA double‐strand break at the TCR locus is associated with off‐target events in human primary T cells. Results: TCRα chain and TCRβ chain knockout leads to high on‐target InDel frequency and functional knockout. None of the predicted off‐target sites could be confirmed experimentally, whereas whole‐genome sequencing and manual Integrative Genomics Viewer (IGV) review revealed 9 potential low‐frequency off‐target events genome‐wide. Subsequent amplification and targeted deep sequencing in 7 of 7 evaluable loci did not confirm these low‐frequency InDels. Therefore, off‐target events are unlikely to be caused by the CRISPR/Cas9 engineering. Conclusion: The combinatorial approach of whole‐genome sequencing and targeted deep sequencing confirmed highly specific genetic engineering using CRISPR/Cas9‐mediated TCR knockout without potentially harmful exonic off‐target effects. Abstract : Exploiting forces of T cells for treatment through genetic engineering of the T‐cell receptor (TCR) redirects specificity, ablates alloreactivity and brings significant progress and off‐the‐shelf options. CRISPR/Cas9‐mediated double‐strand breaks in the TCRα and TCRβ chain are supposed to be a site‐specific TCR knockout. Whole‐genome sequencing and targeted deep sequencing confirmed highly specific DNA engineering without potentially harmful exonic off‐target effects in primary human T cells.